Microstructure, morphology and electrochemical properties of Co nanoflake water oxidation electrocatalyst at micro- and nanoscale - Naseri, Naimeh; Solaymani, Shahram; Ghaderi, Atefeh; Bramowicz, Miroslaw; Kulesza, Slawomir; lu, tefan; Pourreza, Mohammad; Ghasemi, Shahnaz (RSC advances, 2017)
Nowadays, fossil fuel limitations and environmental concerns push researchers to find clean and renewable energy resources. Solar hydrogen production via water splitting reactions in electrochemical and/or photo-electrochemical systems has been accepted as a promising route and efficient electrocatalysts are involved in both. Here, cobalt nanoflakes with an oxide/hydroxide surface and a conductive metallic core are grown on commercially available steel mesh modified with carbon based nanocomposites as a support layer. The portion of reduced graphene oxide sheets was changed from 0 to 100 wt% and the correlation of this concentration with the surface morphology and electro-catalytic activity of the final electrode was studied systematically for the first time. Obtained results revealed the least over potential (224.2 mV) for the sample with 50 wt% rGO in the water splitting reaction which is promising for use in alkaline electrolysis devices. Nowadays, fossil fuel limitations and environmental concerns push researchers to find clean and renewable energy resources.